Nonparametric analysis of time-inconsistent preferences - Browning, M; Crawford, I; Blow, L (University of Oxford, 2017)
This paper provides a revealed preference characterisation of quasi-hyperbolic discounting which is designed to be applied to readily-available expenditure surveys. We describe necessary and sufficient conditions for the leading forms of the model and also explore the consequences the restrictions on preferences popularly used in empirical lifecycle consumption models. Using data from a household consumption panel dataset we explore the prevalence of time-inconsistent behaviour. The sophisticated quasi-hyperbolic model provides a significantly more successful account of behaviour than the alternatives considered. We estimate the joint distribution of time preferences and the distribution of discount functions at various time horizons.